The Influence of Leader-Follower Cognitive Style Similarity on Followers’ Organizational Citizenship Behaviors - Armstrong, Steven J.; Qi, Meng (Frontiers in Psychology, 2020)
While cognitive style congruence has been highlighted as a potentially important variable influencing performance outcomes in work-related contexts, studies of its influence are scarce. This paper examines the influence of leader-follower cognitive style similarity on followers’ organizational citizenship behaviors. Data from 430 leader-follower dyads were analyzed using polynomial regression and response surface analysis. Results demonstrate that congruence of leader/follower cognitive style is a predictor of follower organizational citizenship behaviors. Organizations may therefore benefit from considering issues of similarity of cognitive styles in their attempts to develop effective leader-follower partnerships leading to increased organizational citizenship behaviorsand concomitant improvements in both individual and organizational level success.